2015
DOI: 10.1007/s00404-015-3889-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and hormonal characteristics among four phenotypes of polycystic ovary syndrome based on the Rotterdam criteria

Abstract: The highest AMH levels were found in phenotype A. Phenotype B similar to controls had significantly low AMH compared to other three PCOS phenotypes. Women in the phenotypes D and controls showed significantly lower levels of LH/FSH ratio, total testosterone, and free androgen index, and higher levels of FSH and SHBG compared with phenotype A (P < 0.001). In logistic regression analysis, AMH and LH were predictors for PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
33
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 39 publications
13
33
2
2
Order By: Relevance
“…Positive aspects of this study included the significant number of subjects in the study of a homogeneous Caucasian population, the type A phenotype for PCOS all with the same 3 diagnostic criteria fulfilled where AMH noted to be the highest in this population . All patients had polycystic ovaries on ultrasound, and therefore, it might have expected all of the AMH values to be elevated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive aspects of this study included the significant number of subjects in the study of a homogeneous Caucasian population, the type A phenotype for PCOS all with the same 3 diagnostic criteria fulfilled where AMH noted to be the highest in this population . All patients had polycystic ovaries on ultrasound, and therefore, it might have expected all of the AMH values to be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Positive aspects of this study included the significant number of subjects in the study of a homogeneous Caucasian population, the type A phenotype for PCOS all with the same 3 diagnostic criteria fulfilled where AMH noted to be the highest in this population. 10,16 All patients had polycystic ovaries on ultrasound, and therefore, it might have expected all of the AMH values to be elevated. Why this was not the case is likely due to the observation that AMH values have been shown to be lower in anovulation, and many of these patients may have been anovulatory, although this was not determined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence that women with the PCOS phenotypes A and B have an increased risk of hepatic steatosis as compared with women with PCOS with the nonhyperandrogenic phenotype and compared with healthy controls (83,84). The highest antim€ ullerian hormone levels are also found in patients with classic PCOS (85)(86)(87). Data from 1,297 women with PCOS from Greece have shown that menstrual cycle pattern is more irregular in these women as compared with phenotype D but seems to normalize with ageing (88).…”
Section: ''Classic'' Pcos (Phenotypes a And B)mentioning
confidence: 99%
“…Interviewers also asked participants: at what age their menstrual periods became regular or if it never became regular; and if their periods became regular naturally, because of birth pills, or in some other way. Other PCOS-related symptoms/sequelae such as acne, obesity (weight and height), OC use, history of infertility, age at menarche and age at first birth were also assessed at the interview, and covariates were defined based on the Rotterdam criteria and previous studies regarding clinical features of PCOS [34, 35]. The interviewers also inquired if the participants had physician-diagnosed diseases that are associated with metabolic syndrome such as hypertension, diabetes mellitus and hypercholesterolemia.…”
Section: Methodsmentioning
confidence: 99%